2022
DOI: 10.3390/biom12111556
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Immune-Related Network and Molecular Typing Analysis Defines a Three-Gene Signature for Predicting Prognosis of Triple-Negative Breast Cancer

Abstract: Recent breakthroughs in immune checkpoint inhibitors (ICIs) have shown promise in triple-negative breast cancer (TNBC). Due to the intrinsic heterogeneity among TNBC, clinical response to ICIs varies greatly among individuals. Thus, discovering rational biomarkers to select susceptible patients for ICIs treatment is warranted. A total of 422 TNBC patients derived from The Cancer Genome Atlas (TCGA) database and Molecular Taxonomy of Breast Cancer International Consortium (METABRIC) dataset were included in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Diagnostic signatures focus on the extremes (healthy vs. cancer, stage I vs. stage IV) to increase efficacy 12–15 . Prognostic signatures are developed across the disease spectrum and are often as correlated with the stage of disease as they are with gene expression 70–75 . In fact, most breast cancer signatures that claim to have clinical value do not outperform random gene sets and are rather artifacts of increased proliferation in cancer 51,52 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diagnostic signatures focus on the extremes (healthy vs. cancer, stage I vs. stage IV) to increase efficacy 12–15 . Prognostic signatures are developed across the disease spectrum and are often as correlated with the stage of disease as they are with gene expression 70–75 . In fact, most breast cancer signatures that claim to have clinical value do not outperform random gene sets and are rather artifacts of increased proliferation in cancer 51,52 .…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 13 , 14 , 15 Prognostic signatures are developed across the disease spectrum and are often as correlated with the stage of disease as they are with gene expression. 70 , 71 , 72 , 73 , 74 , 75 In fact, most breast cancer signatures that claim to have clinical value do not outperform random gene sets and are rather artifacts of increased proliferation in cancer. 51 , 52 When a selection of human gene signatures was applied to lungs in our system, each failed to match the ability of our signature to delineate metastatic potential against random gene sets (Figure S10 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene expression and clinicopathological features of patients in the HCC-related TCGA data set were integrated and analyzed for clinical correlation using the R software package "ComplexHeatmap", followed by delineation of a heat map. 25…”
Section: Clinical Correlation Analysismentioning
confidence: 99%
“…[11][12][13] In addition, immune molecules in the TIME have great potential as prognostic biomarkers. [14][15][16] Zhang et al 17 reported that as well as having prognostic significance, a set of immune-related genes in TNBC had important predictive value with respect to immune invasion and the effects of immunotherapy. However, studies to date have not fully elucidated the role of immune genes in TNBC.…”
Section: Introductionmentioning
confidence: 99%